Critical Literacy Sustainability: What Pedagogical Practices? Whose Role? - Thamae Lipolelo; Matee Lihotetso Gloria (Discourse and Communication for Sustainable Education)
In today’s fast-changing world, it is essential to equip English as a Second Language learners with strong literacy skills, empowering them to critically assess information, adjust to technological shifts, and engage in global discussions. However, what remains questionable is the suitable pedagogical practices and the teachers’ and the learners’ roles in sustaining literacy in an education system: this study explored pedagogical practices and investigated both stakeholders’ roles in sustaining literacy among ESL learning. The study employed a mixed-methods approach, drawing on two theoretical frameworks: Legitimation Code Theory and Constructivism. Data collection involved tests, questionnaires, document analysis, focus groups, and observations, with analysis conducted using thematic (Atlas.ti), Excel and ANCOVA via Stata17 in SPSS. Results verified that employing semantic gravity and density sustain critical literacy skills. Notably, the null hypothesis (ℎ0) was rejected, confirming influence of the application of semantic gravity and density on informing critical literacy teaching practices.